Digital Adoption and Financial Performance: Evidence From Indonesian SMEs in Food and Beverage Sector - Kezia Audrey Sazkhya Sinaga; Jenni Irene; Rossalina Christanti (PT. Publikasiku Academic Solution, 2023)
Digital adoption is now starting to be utilized by SMEs business actors. This study aims to examine the impact of digital technology adoption on financial performance. Data collection in this study used a survey of 520 SMEs in the food and beverage sector in Indonesia, data analysis was carried out using the purposive sampling method. The variables of concern in this study are digital finance, digital payments, and digital marketing. Furthermore, financial literacy and financial inclusion are proposed as moderation. The results show that digital finance, digital payments and digital marketing have a positive and significant influence on the financial performance of SMEs, so it can be concluded that SMEs that adopt digital technology tend to have better performance. Furthermore, moderation of financial literacy and financial inclusion are unable to strengthen the relationship between digital finance, digital payments and digital marketing to financial performance. The implication of this research is that it is important for business owners to consider the adoption of digital technology in order to improve financial performance. The number of businesses that experience an increase in financial performance, will also be followed by an increase in the Indonesian economy. The limitations during this study were conducted, such as the number of large SMEs samples that were not comparable to other groups, as well as research results that could not be widely applied to other sectors.